The Process of English Language Teaching in 2013 Curriculum - Arif Bulan; Maman Suryaman; Mardiah Mardiah (Universitas Hamzanwadi, 2020)
This study was motivated by the replacement and implementation of the 2013 curriculum in Indonesia. This study aimed to find out how the process of English language teaching in the 2013 curriculum, what are the teacher's constraints on the English language teaching process, and the efforts by the teachers. This study was a qualitative research. The samples of this study were six teachers from six state high schools in Sleman regency. Data collection in this study used observation, document analysis, and interviews. The data analysis technique used qualitative descriptive techniques. The results of the study indicated that the process of English language teaching using the 2013 curriculum was very good. The process of language teaching had implemented through three steps, starting with the pre-activity, core activity, and post-activity. The process of English teaching was based on process standard in the 2013 curriculum by using a scientific approach as one approach that encourages students to learn actively in developing attitude, knowledge and skill. The obstacles faced by teachers in the process of learning English include less of time, need to adapt to the scientific approach, and lack of 2013 curriculum handbooks. the efforts done by teachers were consultation with the senior teacher and instructor of curriculum 2013, routine discussion in MGMP forum, and searching sources of learning from various sources. In conclusion, the learning process in the 2013 curriculum is carried out based on the standard learning process by using a scientific approach that encourages students to learn actively in developing attitudes, knowledge, and skill.